Prospects for Expanding the Possibilities of Etiotropic Therapy of Acute Respiratory Viral Infections in Primary School Children - K. V. Zhdanov; Yu. V. Lobzin; A. U. Sabitov; E. V. Esaulenko; P. V. Sorokin (Антибиотики и Химиотерапия, 2025)
The aim of the study was to evaluate the efficacy and safety of the drug riamilovir (Triazavirin®), 100 mg capsules, in children aged 6–11 years with a diagnosis of acute respiratory viral infection (ARVI).   Materials and methods. The multicenter study included 260 patients diagnosed with acute respiratory viral infections (ICD-10 codes: J00, J02, J02.9, J04, J04.0, J04.1, J04.2, J06, J06.0, J06.9), confirmed by polymerase chain reaction, in the presence of clinical manifestations. Patients were included in the study after one of their legal representatives and the patient themself (from the age of 10) signed an informed consent to participate in the study. The interval between the appearance of the first symptoms of the disease and the patient's inclusion in the study did not exceed 36 hours.   Results. As a result of a multicenter, randomized, double-blind, comparative, placebo-controlled clinical trial, the efficacy and safety of treatment with riamilovir (Triazavirin®) in children aged 6–11 years with a diagnosis of acute respiratory viral infections were established. A decrease in the duration of the disease was shown when using the drug riamilovir compared with the control group. No serious adverse events were detected during the study.   Conclusion. A multicenter clinical trial has established the high efficacy, safety, and good tolerability of riamilovir in the treatment of primary school-age children (6–11 years old) diagnosed with acute respiratory viral infections. The use of riamilovir in clinical practice as an etiotropic therapy in children aged 6–11 years with a diagnosis of acute respiratory viral infections is recommended due to its high efficacy and safety.